Aplikasi Simulasi dan Main Angklung (Saung) Berbasis Android - Danal Meizantaka Daeanza; Oky Dwi Nurhayati; Dania Eridani (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
The modern way of thinking cause traditional music instruments start to lose its enthusiasm. Today’s generation is more familiar with multimedia features presented by computers. Angklung which is one of the world heritage of musical instruments from Indonesian culture is the one that affected by the rapid technology development. Based on such situation, this research is conducted to design a mobile device application which introduces Angklung. The Application is implemented on a mobile device with Android Operating System. The method used in this research is Multimedia Development Life Cycle (MDLC). The evaluation of this application uses two parameters, the Black-box method, and questionnaire. Black-box method evaluation results showed that this application is running according to specification requirements. The result obtained from the questionnaire with Likert scale showed the average score for each question is 88%. So it can be concluded that the application gains positive feedback and has been qualified to be considered as good.